Promoting artificial meat to improve food security and reduce resource-environment pressure: is it practicable in China? - Yang, Minda; Min, Shi; Nguyen, Trung Thanh; Qing, Ping (Frontiers in Sustainable Food Systems, 2024)
Artificial meat is increasingly recognized as a crucial innovation for addressing global food security challenges and reducing environmental pressures. This study aims to understand the practicability of promoting artificial meat consumption to achieve the dual goals of improving food security and reducing resource-environment pressure by evaluating Chinese consumers’ willingness to pay (WTP) for artificial meat. A discrete choice experiment was conducted via an online survey involving 998 consumers from five representative Chinese cities. The experiment was designed to elicit preferences and WTP for artificial meat. A random information intervention providing positive information about artificial meat was included to examine its impact on consumer choices. The estimation results indicate significantly lower WTP for both cultured and plant-based meat compared to farm-raised meat, with plant-based meat receiving higher WTP than cultured meat. The information intervention notably reduced the WTP gap between artificial meat and farm-raised meat, suggesting that consumer education can positively influence acceptance. The findings suggest that the market introduction of artificial meat in China faces considerable challenges, particularly regarding consumer acceptance and perceived value. While positive information can reduce the disparity in WTP, the practicability of promoting artificial meat to achieve food security and environmental sustainability goals is currently limited. This study contributes to the literature on consumer attitudes towards artificial meat in China and provides critical insights for policymakers aiming to promote the consumption of artificial meat.